2018
DOI: 10.1097/wad.0000000000000241
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function and its Risk Factors Among Older US Adults Living at Home

Abstract: Our results provide an important national estimate for interpreting MoCA scores from individual patients, and establish wide variability in cognition among older home-dwelling US adults. Care should be taken in applying previously-established MoCA cut-points to the general population, especially when evaluating individuals from educationally and ethnically diverse groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
2
11
1
Order By: Relevance
“…We found that older age and decreasing years of education were significantly associated with increased likelihood of a positive screening, which is consistent with the current literature. 24 27 , 42 However, we found that males were more likely to screen positive than females, which has been inconsistent with the current literature of screening in primary care. 43 45 …”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found that older age and decreasing years of education were significantly associated with increased likelihood of a positive screening, which is consistent with the current literature. 24 27 , 42 However, we found that males were more likely to screen positive than females, which has been inconsistent with the current literature of screening in primary care. 43 45 …”
Section: Discussioncontrasting
confidence: 99%
“… 12 The lower rates could be reflective of our choice of screening instrument, changing incidence rates, 23 or our population which was generally younger with more years of formal education, the last two being associated with decreased likelihood of ADRD. 8 , 24 , 25 Alternatively, the unexpectedly low positive screening rate could be a reflection of incidence rates, compared to prevalence rates, given the number of ADRD-related studies our group has conducted in these settings over the past two decades. 8 , 12 , 19 , 26 28 Moreover, recent epidemiological studies have shown a reduction in the incidence rates of dementia, 23 , 29 , 30 and an analysis of the Framingham study has shown a greater decline in younger age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alzheimer’s disease, for example, is already the sixth leading cause of death in the United States (Alzheimer’s Association, 2016), and the social and economic burden of dementia has increased from $18 billion in 1993 to $200 billion in 2010 (Hurd et al, 2013). Prior work has identified adult socioeconomic status, social relationships, and health conditions as key risk factors for cognitive function in later life (Dale et al, 2018). An increasing number of studies have also linked early life factors to later cognition, but they have primarily focused on childhood SES and health as key indicators (Luo & Waite, 2005; Lyu & Burr, 2016; Marden et al, 2017; Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sense of control (self-mastery), the belief that one can master, control, and shape their own life, for example, is found to confer cognitive benefits by helping individuals interfere with reaching goals and cope with stress and strain (Soederberg Miller & Lachman, 2000). Good physical health is yet another adult resource that protects cognitive function (Dale et al, 2018), and early life experiences are known to influence health through a variety of mechanisms, including educational attainment, social connectedness, and self-mastery (Ferraro et al, 2016; Luo & Waite, 2005).…”
Section: Introductionmentioning
confidence: 99%